Peningkatan Kompentensi Pelaku UMKM Di Kabupaten Enrekang Melalui Pelatihan Manajemen - Hasbiyadi Hasbiyadi; Jannati Tangngisalu; Rusni Rusni; Hardiani Hardiani; Mursida Abu (STKIP Andi Matappa, 2022)
This training activity aims to improve the competence of MSME actors in the field of business management and marketing, especially e-commerce marketing. The training was conducted in Enrekang district, South Sulawesi, where the participants were business actors, especially MSME businesses. There were 20 participants who took part in this activity. This activity method is carried out with a training model in the form of counseling about business management and the selection of marketing strategies, especially the right e-commerce marketing. Then the next activity is to carry out a mentoring process in the form of consultation for 6 months. The results obtained by the participants are the knowledge of the products being sold is getting better. The conclusion in this activity is that there are several obstacles that have made it difficult for the trainees to increase their business and compete in the market. From the results of direct and indirect observations, it is indicated that these obstacles are such as business management and their ignorance of e-commerce technology and the use of inappropriate marketing strategies. And the mentoring process carried out made it easier for participants to apply the knowledge they got. The results of this activity will be used as a role model for the campus to carry out similar activities in other places. As well as being a reference material for other parties who carry out community service activities.